Validitas LKS Berbasis SSCS (Search, Solve, Create, and Share) untuk Melatih Keterampilan Berpikir Kritis Siswa - Marlangen, Endang Wahyu; Utami, Septiana Dwi; Samsuri, Taufik (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2021)
In the learning process, effective teaching materials are need so that students can receive material easily. One of the problems faced by teachers when teaching is the teaching materials have not led students to high-order thinking so that the ability in students' critical thinking skills is not optimal. Therefore, it is necessary to develop teaching materials in the form of SSCS-based worksheets (Search, Solve, Create, and Share) so that students can play an active role in the learning process. The purpose of this study is to determine the validity of the developed SSCS-based worksheets (Search, Solve, Create, and Share). This is a descriptive study with an analysis, design and development design adopted from the ADDIE approach consists of five stages, namely (analysis, design, development, implementation and evaluation). The worksheets prepared then validated by 10 validators. The results of the validation of SSCS-based worksheets (Search, Solve, Create, and Share) are 87% with very valid categories. Therefore, it can be concluded that SSCS-based worksheets (Search, Solve, Create and Share) are declared valid.